2013
DOI: 10.1155/2013/787495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Breast Cancer in the Horn of Africa: Case Series—A Pilot Study of Breast Cancer from Eritrea

Abstract: Background. Recently, gene expression profiling and its surrogate immunohistochemistry (IHC) markers classified breast cancer into four distinct molecular subtypes, which have different prognoses, targeted therapies, and/or clinical outcomes. Objective. To conduct a preliminary study, to correlate the clinical pathological profiles and taxonomy of molecular subtypes of breast cancer in Eritrea, in the Horn of Africa. Design. Review of pathology reports from Jan. 1 to Nov. 30, 2009, provided 22 cases of microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Recent studies, however, have shown relatively low proportions of ER- and PR-negative BC: Ethiopia (34.7%), 11 South Africa (37%), 12 Sudan (36%), 13 Nigeria (35%), 14 and Eritrea (32%). 15 These recent findings are comparable with that from African American premenopausal women in the Carolina Breast Cancer Study (39%). 16 A recent systematic review and meta-analysis in Africa showed that the proportion of ER- and PR-negative and human epidermal growth factor receptor 2 (HER2)–positive BC in Africa is highly variable.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Recent studies, however, have shown relatively low proportions of ER- and PR-negative BC: Ethiopia (34.7%), 11 South Africa (37%), 12 Sudan (36%), 13 Nigeria (35%), 14 and Eritrea (32%). 15 These recent findings are comparable with that from African American premenopausal women in the Carolina Breast Cancer Study (39%). 16 A recent systematic review and meta-analysis in Africa showed that the proportion of ER- and PR-negative and human epidermal growth factor receptor 2 (HER2)–positive BC in Africa is highly variable.…”
Section: Introductionsupporting
confidence: 66%
“…We noted a higher proportion of ER- and PR-negative BCs compared with recently published studies in Africa. 11 - 15 , 29 , 30 Publications that directly compared African and white patients show differences in ER status of various magnitudes. Similar to our findings, the result of a higher rate of receptor-negative BC was reported in Tanzania compared with Italian patients 23 ; however, the investigation that compared Sudanese women (from a single institution in Khartoum) with Italian women (from Milan, Italy) 13 and, similarly, Ghanaian women with Norwegian women reported minimal difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation